The religious dimension of users in the practice of health assistance: perception of health professionals: DOI:10.15343/0104-7809.20104430436 - de Souza Alves, Joseane (2010)
Investigation of a qualitative nature aiming at knowing the opinion of health professionals on the influence of spiritualityof users in the process health-disease. We used the focal discussion with professionals of the Serviço de Saúde Comunitária do GrupoHospitalar Conceição [Service of Communitarian Health of Conceição Hospital Group of Porto Alegre, R.S., in the period of September2009. The sample has tried to include the diversity of action areas. The subject of the discussion has been the relationship between healthand spirituality of users in the work of professionals. For data interpretation content analysis was used according to two categories:the influence of spirituality on health and respect as impartiality. Results show that professionals have ambiguous conceptions aboutthe influence of the spirituality of users on their health. Professionals respect that dimension, but they do not use it in treatments;